2006
DOI: 10.7589/0090-3558-42.1.56
|View full text |Cite
|
Sign up to set email alerts
|

Necropsy Findings in American Alligator Late-Stage Embryos and Hatchlings From Northcentral Florida Lakes Contaminated With Organochlorine Pesticides

Abstract: ABSTRACT:Increased American alligator (Alligator mississippiensis) embryo and neonatal mortality has been reported from several northcentral Florida lakes contaminated with old-use organochlorine pesticides (OCPs). However, a clear relationship among these contaminants and egg viability has not been established, suggesting the involvement of additional factors in these mortalities. Thus, the main objective of this study was to determine the ultimate cause of mortality of American alligator late-stage embryos a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Chlorpyrifos, cypermethrin, spinosad, malathion and endosulfan also have similar effects on different organs during embryonic development (Mobarak and Al-Asmari, 2011;Uggini et al, 2010;Anwar, 2003;Pourmirza, 2000). Furthermore, Sepulveda et al (2006) and Singh et al (2007) described malformations in different body structures in alligator and rat embryos when exposed to citrinin, endosulfan and organochlorine insecticides.…”
Section: Resultsmentioning
confidence: 99%
“…Chlorpyrifos, cypermethrin, spinosad, malathion and endosulfan also have similar effects on different organs during embryonic development (Mobarak and Al-Asmari, 2011;Uggini et al, 2010;Anwar, 2003;Pourmirza, 2000). Furthermore, Sepulveda et al (2006) and Singh et al (2007) described malformations in different body structures in alligator and rat embryos when exposed to citrinin, endosulfan and organochlorine insecticides.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, higher rates of thyroid dysfunction, hatching success, egg shell thinning, and gross birth deformities in numerous wildlife populations across the world have been related to habitat contamination (Hamlin & Guillette 2010). In crocodilians, several birth defects related to endocrine system disruption have been observed in a wild population of A. mississippiensis inhabiting a contaminated lake (Guillette & Milnes 2001, Sepúlveda et al 2006. However, no direct relationships between the high level of contaminants and deformities have been proved.…”
Section: Possible Causes Of Agenesismentioning
confidence: 99%
“…Clutch size and hatching success are measures of reproductive performance in oviparous species. Field and laboratory studies suggested that parental exposure to OCCs may contribute to low clutch viability (de Solla et al, 2008;Lundholm, 1997;Rauschenberger et al, 2004Rauschenberger et al, , 2007Sepúlveda et al, 2006). In this background, we conducted a study to estimate the OCC residues present in the eggs of C. latirostris from northeastern Argentina and to determine the relationship between OCC concentrations and measures of reproductive performance.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%